Respuesta :

gmany

Answer:

[tex]\large\boxed{g(-3)+-27}[/tex]

Step-by-step explanation:

[tex]g(x)=-2x^2+3x\\\\g(-3)\to\text{put x = -3 to the equation of a function}\\\\g(-3)=-2(-3)^2+3(-3)=-2(9)-9=-18-9=-27[/tex]

The value of the function g(-3) is -27.

What is a function?

  • In mathematics, it is an expression and rule that defines the relationship between the one independent variable with the another dependent variable.
  • y = f(x) is a function and it states that, there is an unique value of y for every value of x.

Given: Function g(x)

[tex]g(x)=-2x^2+3x[/tex]

Now, we have to find the value of g(-3), for that we will substitute the value of x = -3 in the given equation of the function g(x), hence we get:

[tex]g(-3)=-2(-3)^2+3(-3)\\[/tex]

g(-3) = -27

Therefore, for the given function g(x), the value of g(-3) will be -27.

Learn more about the Functions on: https://brainly.com/question/16406473?referrer=searchResults

#SPJ2